Trauma Kimia Okuli Roper-Hall Derajat IV Bilateral - Purjanto Tepo Utomo; Amanda Nur Shinta P; Banuaji Dibyasakti; Nikolaus Erik Darmawan; Agus Supartoto (Majalah Oftalmologi Indonesia, 2021)
Introduction : Ocular Chemical Trauma is an emergency case and need immediate treatment . The causes vary from work accident to abuse. Treatment is aimed to minimalize surface abbration and preserve eye normal anatomy and physiology. Case Presentation : A 31-year-old man presented with bilateral vision loss with history of unknown liquid exposure to both eyes 2 days prior. Visual acuity was light perception on the right eye and hand movement on the left eye. Ophtalmologic examination presents bilateral palpebral spasms with 3rd grade combustion, bilateral conjunctival chemosis with 360 degree limbal ischemia, lateral canthus symblepharon and bilateral corneal haze. The patient was hospitalized for 33 days. Conclusion : Ocular chemical trauma has a poor visual outcome despite an extensive treament due to damaged limbal stem cell and the following deterioration sequelae.